The Scientific and Methodological Basis of Organizing Psychoprophylactic and Psychocorrectional Work in Applied Psychology - Ibragimovna, Yadgarova Ozoda (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2026)
This article examines the theoretical and methodological foundations of psychoprophylaxis and psychocorrection within the system of applied psychology. The stages of organizing psychoprophylactic activities in educational institutions are analyzed. Furthermore, psychocorrectional interventions, their classification criteria (by tasks, character, and form of organization), and the historical periods of this field's formation are scientifically and theoretically substantiated. Special attention is paid to the laws and decrees of the Republic of Uzbekistan regulating mental health protection. The paper highlights the differentiation between symptomatic and causal correction, as well as general, private, and special psychological interventions based on the activity paradigm.